2013
DOI: 10.1088/0741-3335/55/12/124043
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a metal wall on confinement in JET and ASDEX Upgrade

Abstract: In both JET and ASDEX Upgrade (AUG) the plasma energy confinement has been affected by the presence of a metal wall by the requirement of increased gas-fuelling to avoid tungsten pollution of the plasma. In JET with a beryllium/tungsten wall the high triangularity baseline H-mode scenario (i.e. similar to the ITER reference scenario) has been strongest affected and the benefit of high shaping to give good normalised confinement of H 98~1 at high Greenwald density fraction of f GW ~0.8 has disappeared. In AUG w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
145
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(152 citation statements)
references
References 39 publications
6
145
0
1
Order By: Relevance
“…Compared with results with a C-dominated wall, the operation with the full-W wall in AUG is restricted to higher densities f GW > 0.75 and confinement is on average reduced by 5%-10%. 38 Thus, the lowest H-factors obtained in AUG can be attributed to high gas puff levels required to avoid W-accumulation. For the extrapolation to ITER however, the results of AUG-W with an intact, fresh boronisation and thus higher H 98(y,2) are most relevant as the boron-coated main chamber walls in AUG-W together with the tungsten divertor (typically not affected during a boronisation process) simulate more closely the situation in ITER of a Be main-chamber-wall and a tungsten divertor.…”
Section: -9mentioning
confidence: 99%
“…Compared with results with a C-dominated wall, the operation with the full-W wall in AUG is restricted to higher densities f GW > 0.75 and confinement is on average reduced by 5%-10%. 38 Thus, the lowest H-factors obtained in AUG can be attributed to high gas puff levels required to avoid W-accumulation. For the extrapolation to ITER however, the results of AUG-W with an intact, fresh boronisation and thus higher H 98(y,2) are most relevant as the boron-coated main chamber walls in AUG-W together with the tungsten divertor (typically not affected during a boronisation process) simulate more closely the situation in ITER of a Be main-chamber-wall and a tungsten divertor.…”
Section: -9mentioning
confidence: 99%
“…Measurements from recent JET campaigns with the ILW offer an invaluable opportunity to investigate how the pedestal structure changes with the presence of a metallic wall and its role on confinement. This paper presents a database consisting of deuterium fuelled and nitrogen seeded Type I ELMy H-mode plasmas on JET with the ILW (JET-ILW) [Maddison 2011, Giroud-IAEA-2012, Giroud 2013, Beurskens 2013, Beurskens 2014, Maddison 2014 with the focus on quantifying the pedestal structure. The pedestal width, gradient and height is determined by fitting a modified hyperbolic tangent (mtanh) function [Groebner 1998] to JET High Resolution Thomson Scattering (HRTS) radial profiles of electron temperature and density [Pasqualotto 2004, Frassinetti 2012, Scannell 2011.…”
Section: Introductionmentioning
confidence: 99%
“…A multi-machine review [Beurskens 2013] of three possible mechanisms which could account for the changes in performance observed on JET and AUG concluded that the improvement in performance is not due to an improvement in core confinement nor can it be accounted for due to ion dilution. Instead it is most likely the change in pedestal structure results in the improvement in global performance.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations